The Effectiveness of the Electronic Information System for Official Travel Orders (E-Sppd) in Improving the Administration of Official Travel for Payakumbuh City Government Employees - Azmi, Muhammad Febria; Soemartono, Triyuni; Nenobais, Harry (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Study purpose. The Payakumbuh City Government conducts numerous official travel trips for employees to carry out their duties. Previously, official travel administration was handled manually, but since August 2018, the Payakumbuh City Government has been using the e-SPPD application. This application facilitates online permit applications and evaluations for official travel for ASN. With e-SPPD, the approval and document filing processes are faster and more secure. This study aims to analyze the evaluation results of the implementation of e-SPPD in the Payakumbuh City Government. Materials and Methods. This study uses the DeLone and McLean (2016) effectiveness assessment model, which consists of six dimensions: information quality, system quality, service quality, intended use, user satisfaction, and net benefits. This research was conducted by interviewing relevant informants: the Acting Mayor of Payakumbuh, the Head of the Leadership Administration Sub-Division, the Secretary of the Communication and Information Agency, the Financial Sub-Coordinator, the Payakumbuh City Regional Secretary, and the Payakumbuh City Inspector. Results. The results of this study demonstrate the effectiveness of the e-SPPD information system in administering official travel for civil servants in Payakumbuh City, assessed across six dimensions. The system's quality is considered good, with a simple interface and easy access, although it does not support iOS devices. The system reduces errors and allows tracking of the status of Assignment Letter applications. Security is also good, with two-factor authentication and regular monitoring. Conclusion. The evaluation results demonstrate efficiency and transparency, although there are shortcomings in automatic notifications and the need for additional, regularly updated recapitulation data regarding the official travel budget for each Regional Apparatus Organization. Users are satisfied, but older employees may need assistance and adjustments. Barriers include technology adaptation and concerns about data security. The local government is working to provide training and protect data to support the system.